DUS characterization of rice hybrids and their parental lines using morphological marker - Kumar, Sunil; Marker, S; Chandra, Ramesh; Kumar, Ravindra; Pradhan, S K; Rai, Prashant Kumar (ORYZA-An International Journal of Rice, 2018)
A plant variety is a genetically related plant group obtained by breeder, as a result of long and thoughtful process. A new cultivar is an important means of enhancing production and productivity of cultivated plants, their fruit quality and resistance to diseases,Â thus helping in increasing the excellence of agriculture. Characterization of plant varieties in context of intellectual property rights is stimulated by the recent agreements within the framework of the World Trade Organization (WTO). The requirements of these activities vary, e.g. the varietal registration process involving testing for Distinctness, Uniformity and Stability (DUS) requires that a description of a newly bred variety be produced and compared to all existing varieties in common knowledge. These characters suffer from the limitations of number, interaction with the environment in which the variety grows and subjectivity in decision-making. The genuineness of variety is one of the most important characteristics of quality seed. In addition, seed certification, which forms a link between variety registration and seed production, involve assessment, varietal identification and purity to assure the quality of seed marked to farmer or grower. Characterization of four hybrids such as NARENDRA SANKAR DHAN 2, Rajlaxmi, Ajay and CR Dhan 701 their parental lines such as IR58025A, NDR3026-3IR, CRMS32A, IR42266-29-3R, CRMS31A, CRMS32A, CRL22R and IR42266-29-3R based on distinguishing characters could differentiate the hybrids and parental lines.